Synthesis, Structural Elucidation, and Antibacterial Evaluation of Some New Molecules Derived from Coumarin, 1, 3, 4-Oxadiazole, and Acetamide. (7th September 2016) - Rasool, Shahid; Aziz-ur-Rehman,; Abbasi, Muhammad Athar; Siddiqui, Sabahat Zahra; Shah, Syed Adnan Ali; Hassan, Sidra; Ahmad, Irshad
Abstract : Because of the reported biological activities of coumarin, 1, 3, 4-oxadiazole, and acetamides, some new compounds incorporating these moieties were synthesized and evaluated for their biological potential against Gram-positive and Gram-negative bacteria. In the present work, 4-chlororesorcinol (1 ) and ethyl acetoacetate (2 ) were mixed in a strong acidic medium to synthesize 6-chloro-7-hydroxy-4-methyl-2-oxo-2 H -chromene (3 ) which was subjected to the intermolecular cyclization after consecutive three steps to synthesize 5-[ (6-chloro-4-methyl-2-oxo-2 H -chromen-7-yl)oxy]methyl -1, 3, 4-oxadiazol-2-thiol (6 ). A series of acetamoyl electrophiles, 8a –o, were synthesized from aralkyl/alkyl/aryl amines, 7a –o, in an aqueous basic medium. The final compounds, 9a –o, were synthesized by the reaction of compounds6 and8a –o in DMF/NaH. The synthesized compounds were structurally elucidated by spectral data analysis of IR, 1 H-NMR, and EIMS. The most of the synthesized compounds remained moderate to excellent antibacterial agents. The molecules, 9e, 9j, and9k, were the most efficient ones against all the five bacterial strains taken into account.